2000
DOI: 10.1016/s1097-2765(00)00067-8
|View full text |Cite
|
Sign up to set email alerts
|

Stat5 Is Essential for the Myelo- and Lymphoproliferative Disease Induced by TEL/JAK2

Abstract: STAT5 is activated in a broad spectrum of human hematologic malignancies. We addressed whether STAT5 activation is necessary for the myelo- and lymphoproliferative disease induced by TEL/JAK2 using a genetic approach. Whereas mice transplanted with bone marrow transduced with retrovirus expressing TEL/JAK2 develop a rapidly fatal myelo- and lymphoproliferative syndrome, reconstitution with bone marrow derived from Stat5ab-deficient mice expressing TEL/JAK2 did not induce disease. Disease induction in the Stat5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
217
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 283 publications
(227 citation statements)
references
References 53 publications
9
217
0
Order By: Relevance
“…Ectopic expression of SOCS-1 blocks the constitutive tyrosine phosphorylation of TEL-JAK2 and hence its capacity to phosphorylate downstream targets such as STAT1 and STAT5 necessary for cellular transformation (Schwaller et al, 2000). In addition to functioning as a pseudosubstrate inhibitor of TEL-JAK2, we observed that its steady state expression levels of TEL-JAK were markedly decreased in the presence of SOCS-1.…”
Section: Discussionmentioning
confidence: 70%
“…Ectopic expression of SOCS-1 blocks the constitutive tyrosine phosphorylation of TEL-JAK2 and hence its capacity to phosphorylate downstream targets such as STAT1 and STAT5 necessary for cellular transformation (Schwaller et al, 2000). In addition to functioning as a pseudosubstrate inhibitor of TEL-JAK2, we observed that its steady state expression levels of TEL-JAK were markedly decreased in the presence of SOCS-1.…”
Section: Discussionmentioning
confidence: 70%
“…STAT5A1*6 was not used owing to its too strong oncogenic potential in vivo as reported earlier. 36 The transduction efficiencies of NRAS G12V , STAT5A#2 and MLL-ENL were 30-50, 20-40 and 5-10%, respectively, as determined by GFP expression (data not shown).…”
Section: Activation Of Ras-mapk Cascade Enables Hf6 Cells To Grow Witmentioning
confidence: 92%
“…35 Murine BMT assays were performed as described previously. 36 In brief, retroviral supernatants were generated by transient cotransfection of 293T cells with the MSCV2.2-Gateway-IRES-GFP-BCR-ABL 37 or FLT3-ITD/51 38 constructs and packaging construct using Superfect (QIAGEN). The viral titer was estimated by infecting Ba/F3 cells with serial dilutions of viral supernatant and percentage of GFP-positive cells was determined by flow cytometry 48 hours postinfection.…”
Section: Micementioning
confidence: 99%